Normative macular thickness measurements in healthy Saudi paediatric population using optical coherence tomography - Alshehri, Abdulaziz Mohammed (International Surgery Journal, 2025)
Background: The purpose of the study was to establish normative data for macular thickness in a healthy Saudi pediatric population using Cirrus HD- optical coherence tomography (OCT) and to analyze the effects of age and gender on macular thickness. Methods: A cross-sectional study was conducted on 350 eyes of 175 Saudi children aged 6–18 years. Participants underwent a comprehensive ophthalmic examination, including vision assessment, refraction, fundus examination, intraocular pressure measurement, and macular thickness measurement using Cirrus HD-OCT. Macular thickness was measured in different quadrants following the early treatment diabetic retinopathy study (ETDRS) map and analyzed by age and gender. Results: The mean macular thickness was 281.3±12 µm, and the mean spherical equivalent refraction was -0.31±1.75 diopters (D) (range: -2.50 to +2.25 D). The parafoveal area was the thickest, followed by the perifoveal area and the central subfield (CSF) thickness (p<0.001). The nasal quadrant of the macula was the thickest, followed by the superior, inferior, and temporal quadrants in both the parafoveal and perifoveal regions. No statistically significant differences were observed between genders or age groups. Conclusions: This study provides normative data for macular thickness in Saudi children, which will aid in the early diagnosis and monitoring of macular disorders in this population. The findings suggest that gender and age have no significant impact on macular thickness measurements in pediatric patients.